Judicial pluralism in the Malaysian legal system - Kayadibi, Saim (Islamic Book Trust, 2011)
Malay society, beside its determination to preserve its own traditions, has allowed other communities to live freely according to their own cultural values and traditions. Diversity is a source of cultural and social wealth that reflects an extraordinary degree of freedom in both legal and cultural richness. Such features resemble the Ottomans’ approach. Malay society has apparently interiorized the value of diversity. Its people believe that for peace, freedom, tolerance, and strength between the different groups to continue, judicial pluralism must be maintained. In connection with this, the Malay legal system has been shaped by different legal systems, among them Islamic law, which has been implemented as per the society’s request at will as a part of life in a natural way, the legal systems of Western colonial powers rather have been used by force on demand. In contrast, the Ottomans’ Majallah al-Ahkam al-‘Adliyyah, the Hanafi legal code of Qadri Pasha (later called the Majallah Ahkam Johor), and the Undang-undang Sivil Islam were all used as the main source of judicial matters in the courts. In this paper, the historical development of the Malay legal system is analyzed and the following themes are elaborated upon: Malaysia’s constitutional law, customary law, and tribal legal systems; Shari‘ah and civil court procedures; the first contacts with Islamic law; the influence of Portuguese, Dutch, and English law; and the Turk-Malay connection and strong relationships.